2011
DOI: 10.1007/s00420-011-0687-7
|View full text |Cite
|
Sign up to set email alerts
|

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8

Abstract: This study demonstrated that urinary MEAA can be used as an accurate biomarker of exposure for JP-8 workers and clearly distinguished the differences in JP-8 exposure by workgroup category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…The BMA and PMA results of this study are summarized in Table 1 and are compared to a summary of MEAA data that were collected and reported previously (B'Hymer et al 2012). The numbers of samples determined as positive for the presence of the BMA biomarker, that is, above the test method's LOD (0.5 ng/ml), were 96 (98.0%), 37 (97.4%), and 58 (95.1%) for the high, moderates and low exposure work-group categories, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The BMA and PMA results of this study are summarized in Table 1 and are compared to a summary of MEAA data that were collected and reported previously (B'Hymer et al 2012). The numbers of samples determined as positive for the presence of the BMA biomarker, that is, above the test method's LOD (0.5 ng/ml), were 96 (98.0%), 37 (97.4%), and 58 (95.1%) for the high, moderates and low exposure work-group categories, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Because of the low frequency of use of the parent compound, the MEAA metabolite has not been detected in the general population and should not appear in any significant quantity in a control population. MEAA has been studied for use as a biomarker previously in both humans (B'Hymer et al 2012) and animals (B'Hymer et al 2005a;Richards et al 1993). It has also been demonstrated that MEAA is the urinary metabolite best suited for use as a short-term biomarker for exposure to 2-(2-methoxyethoxy)ethanol (Richards et al 1993).…”
Section: Hhs Public Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…In industry, alkoxyethanols are often used as gasoline additives to improve the octane number, reduce pollution, and upgrade product quality . For instance, in the formulation of JP-8, a kerosene fuel widely used by the U.S. Air Force, 2-(2-methoxyethoxy) ethanol is usually added as a deicing agent. , The compound is also used as an ink additive . However, the potential occupational health concern caused by 2-(2-methoxyethoxy) ethanol exposures cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Early in 2003, B’Hymer et al realized the quantitative determination of MEAA in human urine with gas chromatography-mass spectrometry (GC-MS) systems . To date, gas chromatography (GC) methods have been developed into the main techniques applied to assess the biomarker MEAA. ,, Nevertheless, these detection methods require cumbersome pretreatment operations and relatively sophisticated instruments. Therefore, the development of a highly sensitive, easy-to-operate, and low-cost method for the rapid and accurate determination of MEAA in human urine and serum is becoming increasingly urgent.…”
Section: Introductionmentioning
confidence: 99%